Hospital admissions in poorly nourished, compared with well‐nourished, older South Australians receiving 'Meals on Wheels': Findings from a pilot study. (4th March 2013) - Luscombe‐Marsh, Natalie; Chapman, Ian; Visvanathan, Renuka
<x xml:space="preserve">Abstract</x> Aim To evaluate whether 'Meals on Wheels' (MOW) improves health and reduces hospital admissions in poorly nourished (PN) older people. Methods Two hundred and fifty older South Australians were retrospectively classified: (i) PN (MNA score <24) receiving MOW (MOW PN); (ii) PN not receiving MOW (non‐MOW PN); and (iii) well‐nourished (WN). Data regarding their health were compared. Results Health outcomes at baseline for MOW PN and non‐MOW PN were not different, but both were worse than the WN. Over 12 months, weight loss was ∼2–3 times greater in both PN than WN groups. Hospital admissions were not different for MOW PN compared with non‐MOW PN and WN, but non‐MOW PN had 2.9 as many admissions and spent 5 days more in hospital than WN (all Ps < 0.05). Conclusion Providing MOW to nutritionally vulnerable older people may not prevent age‐related decline in health, although a potential reduction in hospital admissions warrants investigation.